2006
DOI: 10.1590/s1516-31802006000500011
|View full text |Cite
|
Sign up to set email alerts
|

Descending mediastinitis: a review

Abstract: CONCLUSION:Since DM is a lethal condition if not promptly treated, it must always be considered to represent an emergency situation. deep neck into three major fascial pathways by which oropharyngeal infections can spread towards the mediastinum (Table 1). The three layers are the pretracheal or superfi cial, visceral and prevertebral layers. In turn, there are three main fascial pathways. The fi rst of these is the pretracheal pathway, which is anterior to the trachea and ends in the anterior mediastinum at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 27 publications
1
26
0
5
Order By: Relevance
“…Because polymicrobial CNF/DNM is more commonly seen, antibiotics need to be broad enough to cover Gram‐positive cocci,Gram‐negative rods, and anaerobic bacteria. Several empirical regimens include piperacillin–tazobactam and vancomycin and clindamycin with ceftriaxone or carbapenems have been described in the published reports . It is suggested that, in cases of DNM complicated by streptococcal toxic shock syndrome, the use of protein synthesis inhibitors such as clindamycin proves more effective than penicillin .…”
Section: Treatmentmentioning
confidence: 99%
“…Because polymicrobial CNF/DNM is more commonly seen, antibiotics need to be broad enough to cover Gram‐positive cocci,Gram‐negative rods, and anaerobic bacteria. Several empirical regimens include piperacillin–tazobactam and vancomycin and clindamycin with ceftriaxone or carbapenems have been described in the published reports . It is suggested that, in cases of DNM complicated by streptococcal toxic shock syndrome, the use of protein synthesis inhibitors such as clindamycin proves more effective than penicillin .…”
Section: Treatmentmentioning
confidence: 99%
“…The vena caval foramen is not considered part of the continuum because its adherence to the vein wall does not allow subserous tissue [3]. Nevertheless, this foramen has occasionally been described as a potential pathway for bidirectional disease migration, both in retroperitoneal abscesses [11] and in cases of descending mediastinitis [14]. In addition, the caval lumen by itself can act as a transphrenic pathway, usually described in (macroscopic) transvenous spread of some neoplastic diseases [4] (Fig.…”
Section: Vena Caval Foramenmentioning
confidence: 99%
“…Antibiotic therapy should be started immediately and be broad enough to cover Gram-positive cocci, Gram-negative rods and anaerobic bacteria. Empirical treatment regimens include piperacillintazobactam and vancomycin, clindamycin with either ceftriaxone or ceftazidime, or in penicillin-allergic patients, a quinolone plus clindamycin [57]. Once sensitivities are known, therapy can be tailored accordingly.…”
Section: Microbiology and Antibiotic Therapymentioning
confidence: 99%